2022
DOI: 10.1155/2022/7539546
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Mechanical Behaviour of LM6 Aluminum Alloy Hybrid Composites Processed Using Stir Casting Process

Abstract: The stir casting process produces boron nitride (B4N) and fly ash-based LM6 metal matrix composites. This hybrid composite was fabricated by varying fly ash from 3% to 15% with an increase of 3%. While the other reinforcement B4N concentration was kept constant as 3%. The morphology of the metal matrix composite is analysed using a light optical microscope. The microstructure analysis shows the uniform distribution of hybrid reinforcement throughout the matrix, and only a few clusters are found in the matrix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Aluminum alloys possess high specific stiffness, high specific strength, excellent corrosion resistance, and easy processability [10][11][12]. It is not only widely used in aerospace, rail transit, shipbuilding, automotive, and military fields, but its development trend is towards larger sizes, integration, complex shapes, and high precision, making it the first choice for lightweight design [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloys possess high specific stiffness, high specific strength, excellent corrosion resistance, and easy processability [10][11][12]. It is not only widely used in aerospace, rail transit, shipbuilding, automotive, and military fields, but its development trend is towards larger sizes, integration, complex shapes, and high precision, making it the first choice for lightweight design [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Widyanto et al [9] analysed the efect of the concentration of HNO 3 , H 2 SO 4 , and HCl on the carbon steel through an immersion corrosion test, and the result revealed that the increase in the corrosion rate was observed during the time of increasing the concentration. Aluminium composites are used in many chemical industrial applications because of their superior mechanical properties such as high tensile strength, hardness, toughness, and impact strength [10,11]. Aluminium is an abundantly used industrial material because of its automobile and aerospace applications.…”
Section: Introductionmentioning
confidence: 99%